(untitled) - Aronson, Elliot (New York, 1997)
Written by three experts in the field, this book provides an insight into the history and process of social psychology, drawing upon the combined experience of the three authors. This edition has been brought up to date with recent developments.
Keywords: Social psychology,Tâm lý học xã hội